Converse flexoelectricity yields large piezoresponse force microscopy signals in non-piezoelectric materials - Amir Abdollahi (Nature Portfolio, 2019)
Piezoresponse force microscopy (PFM) is widely used to study piezoelectric properties of materials. Here, the authors not only show that PFM measurements will yield a signal even in non-piezoelectric materials via induced flexoelectricity, but also introduce a protocol to distinguish these from real signals.